Ideal partners: the farmer, the planner and the banker - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
They call biodiversity our insurance policy for life . So, in the farmers fields where biodiversity is essential and yet under threat, let s talk about the insurance premiums, let s talk money. Biodiversity, or more correctly, biological...